Effect of Co substitution for La on hydrogen storage properties and thermal stabilities of amorphous Mg60Ni30La10−xCox (x = 0, 2 and 4) alloys prepared by melt spinning. (February 2014) - Lv, P.; Wang, Z.; Zhou, H.; Deng, J.; Yao, Q.; Zhang, H.
<x content-type="archive" xml:space="preserve">Abstract</x> A comparison of the hydrogen storage properties and thermal properties of amorphous Mg60Ni30La10−xCox hydrogen storage alloys prepared by melt spinning has been investigated. A, B and C were used to represent each alloy composition when x = 0, 2 and 4 respectively. Their microstructures, the hydrogen storage properties and the thermal stabilities were analysed by X-ray diffraction (XRD), PCTPro2000 and differential scanning calorimetry (DSC) respectively. After hydrogenation of Mg60Ni30La10−xCox (A, B and C) samples at 573 K under 2 MPa hydrogen pressure, XRD pattern results indicate the formation of new phases of MgH2 (A, B, C), Mg2NiH4 (A, B, C), La4H12·19 (A, B, C), Mg2Ni0·9Co0·1H4 (B), Mg2NiH0·26 (C) and Mg2CoH2 (C). It is observed that the experimental data of hydrogen desorption kinetics at 523, 573 and 623 K are well fitted through Avrami–Erofeev equation, and the hydrogen desorption kinetics is in the order of C>B>A. In addition, with increasing Co content, alloy C has the maximum hydrogen absorption capacity of 3·05 wt-% and the maximum hydrogen desorption capacity of 2·85 wt-%. Based on the results of DSC analysis, dehydrogenation activation energies of these alloys are determined to be 98·31±2·82 kJ mol−1 (A), 96·33±5·61 kJ mol−1 (B) and 78·99±2·98 kJ mol−1 (C), which are in accordance with the results of hydrogen desorption kinetics.